Kinematic characteristics of the tennis serve from the ad and deuce court service positions in elite junior players - Fett, J.; Oberschelp, N.; Vuong, J. L.; Wiewelhove, T.; Ferrauti, A. (PLOS ONE, 2021)
Purpose: According to the official rules of the International Tennis Federation, players have to serve alternately from two different positions: the deuce (right, D) and the ad court (left, AD) side. This study aimed to compare body and ball kinematics of flat serves from both service sides. Methods: In a controlled, semi-court laboratory setting, 14 elite male junior players served eight flat first serves to a target field directed to the receiver`s body from both service positions in a matched and counterbalanced order. An 8-camera-Vicon-System was used to capture the 3D-landmark trajectories. Results: The mean service velocity was found to be similar on both sides (D: 151.4 ± 19.8 vs. AD: 150.5 ± 19.4 km/h), while multiple characteristics of the serve and ball kinematics differed significantly (p < .05). At starting, the front-foot angle relative to the baseline (D: 39.7±17.6° vs. AD: 31.1±17.4°) and lateral distance between the feet (D: 16.3 ± 12.9 cm vs. AD: 26.2 ± 11.9 cm) were significantly different. During the service, upper torso range of motion from maximum clockwise rotation until impact was significantly greater on the deuce court (D: 130.5 ± 19.8° vs. AD: 126.7 ± 21.1°). This was especially pronounced in foot-back technique players. Further, differences in the lateral ball impact location (D: 30.0 ± 24.1 cm vs. AD: 10.3 ± 23.3 cm) were observed. Conclusions: Changing the service side affects the serve and ball kinematics in elite junior tennis players. Our results underline biomechanical differences regarding the starting position (feet and upper torso) as well as the movement and ball kinematics which could be relevant for skill acquisition, injury prevention and performance enhancement.